Jindong Bridge: Suspension Bridge with Steel Truss Girder and Prefabricated RC Deck Slabs in China. Issue 2 (3rd April 2019) - Zhang, Wenming; Liu, Zhao; Xu, Song
Abstract: The Jindong Bridge, crossing the Jinsha River in Yunan Province, China, is a suspension bridge with a main span of 730 m. In this paper, the design and construction of this bridge are introduced. Both tunnel-type and gravity-type anchorages were applied. For installations of main cable strands, the relative altitude difference method was used based on quantified inter-strand distances to guarantee sufficient accuracy. In the erection of steel truss girder, segments were connected by temporary hinges. During the installation of RC deck slabs, temporary hinges of girder segments were converted into permanent rigid connections at appropriate moments, which were determined by calculation; half deck slabs were installed symmetrically from both girder ends to the midspan to generate a channel and the rest deck slab was installed in opposite direction. These structural components and construction technologies, as discussed in this paper, represent a suitable choice for other suspension bridges in mountainous areas.